La falta de valor de la jurisprudencia como ciencia - Kirchmann, Julius Hermann von (Historia del Derecho, 2021)
Title of a conference given by Kirchmann in the Berlin Legal Society in 1847 and later successfully published in 1848. The sentence there included ("three rectifying words by the legislator, and entire libraries would become completely useless") established Kirchmann as a decisive reference and was made popular under the name of "Kirchmann's curse". His rejection of legal positivism and German Historical School placed him near social naturalists, who also criticized both the distance of Legal Science from actual legal issues and its strong dependence on inadequate positive law. Kirchamann's thought is, therefore, characterized by the denial of the validity of Legal Science.